The Impact of Brand Credibility on The Brand Reputation of Teh Botol Sosro Brand - Hamdani, Rezki; Yuliana, Lingga (Pusat P2M Politeknik Negeri Batam, 2024)
The focus of this study is to examine how brand credibility affects brand reputation using Teh Botol Sosro as a case study. Methods of quantitative description are used in this study. The research employed purposive sampling, whereby the participants were selected based on their knowledge of and past purchases of Teh Botol Sosro products, which were to be made between July 2023 and March 2024. In all, one hundred respondents took part in this study. Version 3.3.9 of the Smart PLS analysis program is used to process partial least squares, which are employed in data analysis in research. Respondents were given a Google Form questionnaire with a scale from 1 to 4 that included the options for strongly disagree, disagree, agree, and highly agree. The study's findings indicate that brand reputation is influenced by brand credibility.